Zum sexuellen Missbrauch in der katholischen Kirche Kritik am Münchener Missbrauchsgutachten von 2022 - Losert, Matthias (Young Academics: Rechtswissenschaft, 2023)
In 2022, the Archdiocese of Munich and Freising commissioned the Munich law firm Westphal Spilker Wastl to prepare a report on sexual abuse in their diocese. Dr. Matthias Losert has dealt in detail with the 1,893-page expert opinion. With precise reasoning and great legal expertise, he proves that the Munich abuse report has considerable deficits and that the presumption of innocence was not observed in many cases. The author thus makes an important contribution to objectifying the debate on sexual abuse in the Catholic Church.